Influence of microstructure and mechanical properties of TiC reinforced magnesium nano composites. (2020) - Anbuchezhiyan, G.; Mohan, B.; Kathiresan, S.; Pugazenthi, R.
Abstract: In the present study, an effort has been made to synthesize TiC reinforced magnesium nanocomposites by varying its weight percentage (3%, 6% and 9%) using powder metallurgy for marine applications. The compaction pressure was maintained at 350 MPa for 15 min at 250 °C followed by sintering process. Sintering temperature was maintained at 650 °C in argon protected atmosphere for 8 hrs. Optical microscope and scanning electron microscopy (SEM) have been used to study the microstructure of magnesium nanocomposites. Vickers micro hardness test and ASTM-E9 standards have been used to evaluate the hardness and compressive properties of magnesium nanocomposites. The microstructure of synthesized magnesium nanocomposites revealed that the reinforcement particles are homogeneously distributed in the magnesium matrix without indication of cluster and they appeared as a lamellar precipitates during diffusion. The increase in percentage of reinforcement increases its compressive strength and hardness of magnesium nanocomposites due to the inclusion of stiffer and stronger reinforcement in matrix alloy. B117 salt spray technique was utilized to study the corrosion behavior of magnesium nanocomposites. It has been observed that the corrosion properties of magnesium nanocomposites significantly increased to a maximum of 46% compared with monolithic AZ91D magnesium material.